ECO-FRIENDLY MANAGEMENT OF LEAF SPOT OF GREEN GRAM CAUSED BY CERCOSPORA CANESCENS (Journal of Plant Disease Sciences, 2024)
The green gram crop is affected by several diseases and the Cercospora canescens causing leaf spot is one of the major diseases causing significant losses. In vitro evaluation of different bioagents and phyto-extracts was carried out to test their efficacy against the test pathogen Cercospora canescens. The seven bioagents (5 fungal and 2 bacterial) viz., Trichodermaasperellum, T. harzianum, T. virens, T. koningii, Aspergillus niger, Pseudomonas fluorescens and Bacillu subtilis were evaluated in vitro for their antifungal activities against leaf spot disease of green gram. Trichoderma harzianum, T. asperellum and T. virens showed effective mycelial growth inhibition i.e. 89.81%, 88.80% and 82.65% respectively, which were significantly superior to the untreated control. Among the seven phyto-extracts tested, the treatments of neem leaf extract and garlic clove extract showed effective mycelial growth inhibition i.e.84.81 % and 82.04 %, respectively which were significantly superior over the untreatedcontrol.
Keywords: Bio-agents; Cercospora canescens; Green gram; Phyto-extracts